2022
DOI: 10.21203/rs.3.rs-1774535/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal Rainfall Projection in Majalaya basin, West Java, Indonesia under CMIP6 Scenarios

Abstract: In this study, a Coupled Model Intercomparison Project Phase 6 (CMIP6), from the newest set of General Circulation Models (GCMs), was used to assess the spatiotemporal variability in rainfall regimes over the Majalaya basin in West Java, Indonesia. Twenty grid points of the gridded-based daily rainfall from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) datasets spanning from 1981 to 2014 were extracted. For the future projection, a set of 23 GCMs from the Shared Socioeconomic Path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Rapid urbanization, overpopulation, climate change, extreme precipitation events, aging infrastructure, and low standards of stormwater drainage networks can threaten people's lives, properties, and the environment [54]. Several studies have studied some of Majalaya's problems, such as microplastic problems in drainage [55], the distributions of unconfined aquifers [56], the changes in rainfall characteristics in the Majalaya Basin that cause climate change [14], and the modeling of the 2018 Majalaya, and the floods caused the most extensive losses [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid urbanization, overpopulation, climate change, extreme precipitation events, aging infrastructure, and low standards of stormwater drainage networks can threaten people's lives, properties, and the environment [54]. Several studies have studied some of Majalaya's problems, such as microplastic problems in drainage [55], the distributions of unconfined aquifers [56], the changes in rainfall characteristics in the Majalaya Basin that cause climate change [14], and the modeling of the 2018 Majalaya, and the floods caused the most extensive losses [12].…”
Section: Discussionmentioning
confidence: 99%
“…The subdistricts are all parts of Bandung Regency of West Java Province. The area is known for the textile and agriculture industries that support West Java's economy [9,12,13]. Although the Majalaya area has an important economic function, it has experienced flooding nearly every year since the 1970s.…”
Section: Area Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Floods in Majalaya occur almost every year since 2008 [6]. Usually, floods occur in a relatively short period with depths ranging from ankle-high to 1 m [7]. A flood incident in Majalaya on 22 February 2018 inundated the Majalaya area of 5.35 km² with a peak discharge of 155.82 m³/s.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that most of the rivers in the UCR have more than one ratio, with some classified as severely damaged. Rohmat [3,10] also worked in the Majalaya region and studied areas vulnerable to yearly flooding. As Majalaya is a vital component of the economy of the Bandung Metropolitan Area, the study intended to recreate the devastating flood that occurred on February 22, 2018, damaging a significant amount of property and the surrounding area.…”
Section: Introductionmentioning
confidence: 99%